Impact of chemical treatments on Leuconostoc bacteria from harvested stored cane/stale cane - Misra, Varucha (Biotechnol Rep (Amst), 2020)
Post-harvest sucrose losses are always a critical problem for sugar industries. A predominant factor which is causing these post-harvest losses that affects sugar recovery is the bacterium Leuconostoc spp. This study aims to check the efficacy of certain chemical treatments in reducing the proliferation of this bacterium. Our study based on a Leuconostoc-specific media revealed that application of 0.5 % aqueous solution of benzalkonium chloride and sodium metasilicate (BKC + SMS), formaldehyde, glutaraldehyde, sodium chloride and pine oil showed significant reduction in zone of proliferation. Considering formaldehyde and glutaraldehyde as control, the most effective treatments were chemical formulations of benzalkonium chloride along with sodium metasilicate, pine oil and sodium chloride in checking the proliferation of this bacterium. The application of these treatments has an immense potential in the sugar industry for reducing post-harvest sugar losses.